2019
DOI: 10.1051/0004-6361/201834923
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and radiative transfer modeling of propylene oxide

Abstract: Context. The recent identification of the first complex chiral molecule, propylene oxide (PrO) in space opens up a new window to further study the origin of homochirality on the Earth. There are some recent studies to explain the formation of PrO however additional studies on the formation of this species are needed for better understanding.Aims. We seek to prepare a complete reaction network to study the formation of propylene oxide in the astrophysically relevant conditions. Based on our results, a detailed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…Furthermore, Bergantini et al revealed that PO can be synthesized within the (few hundred nanometers wide) ice-phase coating interstellar grain in molecular clouds at 10 K, followed by sublimation once the temperature of the grains increases with the birth of the central star . This astrochemical model predicting the fractional abundances of PO in cold material in front of Sgr B2­(N) agreed with the observed astronomical abundances in Sgr B2­(N) along with the error limits ( n PO / n H 2 = 10 –12 –10 –10 ), which might be converted into the PO concentration of 10 –26 –10 –24 mol/dm 3 by using the H 2 number density value of 10 7 molecules/cm 3 . , In addition, the typical water abundance is about (1.2–8) × 10 6 relative to H 2 , which is about 4–6 orders of magnitude larger than that of PO …”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Furthermore, Bergantini et al revealed that PO can be synthesized within the (few hundred nanometers wide) ice-phase coating interstellar grain in molecular clouds at 10 K, followed by sublimation once the temperature of the grains increases with the birth of the central star . This astrochemical model predicting the fractional abundances of PO in cold material in front of Sgr B2­(N) agreed with the observed astronomical abundances in Sgr B2­(N) along with the error limits ( n PO / n H 2 = 10 –12 –10 –10 ), which might be converted into the PO concentration of 10 –26 –10 –24 mol/dm 3 by using the H 2 number density value of 10 7 molecules/cm 3 . , In addition, the typical water abundance is about (1.2–8) × 10 6 relative to H 2 , which is about 4–6 orders of magnitude larger than that of PO …”
Section: Introductionsupporting
confidence: 62%
“…Having the adsorption isotherms calculated, we try to address the question whether the adsorption of PO on amorphous ice is a relevant process under interstellar conditions, in other words, whether the typical concentration of propylene oxide in the ISM corresponds to a non-negligible surface coverage at the temperatures considered. The typical concentration of PO in Sgr B2­(N) is thought to be in the range 0.01–1 molecules/dm 3 . Estimating, on the other hand, the gas phase concentration of PO that corresponds to a certain surface coverage requires knowing the saturated vapor pressure at the temperature considered. The temperature dependence of p 0 can be estimated through the Antoine equation, i.e. where the value of p 0 is in kPa units, and A , B , and C are the Antoine parameters, having the values of A = 6.09921, B = 1066.383 K, and C = −46.846 K for PO .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher densities, opacities become so low that the lines would be undetectable. Finally, we note that a non-LTE model for propylene oxide was presented recently by Das et al (2019). In their work, the authors employed the collisional rate coefficients of CH 3 OH with H 2 , which is obviously a crude approximation to mimic the CH 3 CHCH 2 O−H 2 system.…”
Section: Non-lte Modellingmentioning
confidence: 99%
“…Among them several ankan.das@gmail.com prasanta.astro@gmail.com species are marked as the precursor to biomolecules. Study of the pre-biotic molecules is always fascinating as they involved in the formation of amino acids, proteins, and the basic building blocks of life (Chakrabarti & Chakrabarti 2000a,b;Das et al 2008;Garrod 2013;Chakrabarti et al 2015;Majumdar et al 2015;Das et al 2019). Protein synthesis occurs through peptide bond formation (Goldman et al 2010).…”
Section: Introductionmentioning
confidence: 99%